Biomimetic nanoengineered scaffold for enhanced full-thickness cutaneous wound healing. (1st April 2021) - Zandi, Nooshin; Dolatyar, Banafsheh; Lotfi, Roya; Shallageh, Yousef; Shokrgozar, Mohammad Ali; Tamjid, Elnaz; Annabi, Nasim; Simchi, Abdolreza
Graphical abstract: Image, graphical abstract Abstract: Wound healing is a complex process based on the coordinated signaling molecules and dynamic interactions between the engineered scaffold and newly formed tissue. So far, most of the engineered scaffolds used for the healing of full-thickness skin wounds do not mimic the natural extracellular matrix (ECM) complexity and therefore are not able to provide an appropriate niche for endogenous tissue regeneration [1] . To address this gap and to accelerate the wound healing process, we present biomimetic bilayer scaffolds compositing of gelatin nanofibers (GFS) and photocrosslinkable composite hydrogels loaded with epidermal growth factors (EGF). The nanofibers operate as the dermis layer, and EGF-loaded composite hydrogels acted as the epidermis matrix for the full-thickness wound healing application. The hydrogels are composed of gelatin metacryloyl (GelMA) modified with silicate nanoplatelets (Laponite). To overcome the challenges of transdermal delivery of EGF, including short half-life and lack of efficient formulation precise, controlled delivery was attained by immobilization of EGF on Laponite. It is shown that the addition of 1wt% silicate nanoplatelet increases the compressive modulus of the hydrogels by 170%. In vitro wound closure analysis also demonstrated improved adhesion of the scaffolds to the native tissue by 3.5 folds. Moreover, the tunable hemostatic ability of the scaffolds due to the negatively charged nanoplatelets is shown. In an established excisional full-thickness wound model, an enhanced wound closure (up to 93.1 ± 1.5%) after 14 days relative to controls (GFS and saline-treated groups) is demonstrated. The engineered adhesive and hemostatic scaffolds with sustained release of the growth factors have the potential to stimulate complete skin regeneration for full-thickness wound healing.